Analisis Percepatan Terhadap Waktu Proyek (Study Kasus : Kantor Dinas SKPD Gedung B3 Di Tenayan Raya) - Pratama, Aditya; Taufik, Hendra (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Project implementation have always refers to the construction assumption and forecast while time plans and schedule were made, Therefore, the contruction problem will arise if there is a discrepancy between plan and assumptions comparing to the actual project. Delays of project implementation is generally always lead to adverse consequences both for the owner and contractor. The project the (SKPD) Unit City Government of Pekanbaru in Riau is having a delay of 75 days. The Best construction time acceleration is 45 days. Construction acceleration can be conducted by 3 alternatives solutions such as: overtime alternative, equipment and workers addition alternative, and shift system alternative. The analysis started from the critical path. Network project the analysis, was obtained from the cost due to delay stands at Rp. 4.761.786.975,00. Cost of construction acceleration caused by overtime alternative is Rp. 2.152.360.596,00 with a total 11.136 hours of extra work for workers, cost of construction acceleration by the workers and equipments additionionally for alternative result Rp. 2.434.965.492,00 with a total 14 new workers, with additional of 2 new equipment units. Cost of construction acceleration from shift alternative is Rp. 2.434.965.492,00 with a total of 14 new workers, a total 2 of equipment units. In conclusion, the most effective construction acceleration method is overtime alternative, obtained the minimum financial loss and recommended to use for the construction acceleration.Keywords : construction delay, construction cost, duration shortening, overtime, work equipment and workers additional.